Studi Literatur : Efektifitas dan Kelayakan Penggunaan Media Pembelajaran Berbasis Powtoon dalam Pembelajaran Fisika - Dwitri Pilendia (Jurnal Ilmiah Wahana Pendidikan, 2022)
Powtoon is one of the new presentation applications that is currently widely used to develop learning media. In this study, a literature study will be conducted on the feasibility and effectiveness to the use of Powtoon-based learning videos in physics learning. The research was conducted by reviewing research results that have been published in national and international journals based on search results on Google Scholar. The results showed that the average results of developing Powton-based learning media in physics learning were in the appropriate category and very feasible to be used in learning. The results of student responses were very positive and student learning outcomes increased after using Powtoon-based learning videos